Remembering Paul: ancient and modern contests over the image of the Apostle - White, Benjamin L. (Oxford University Press USA - OSO, 2014)
Who was Paul of Tarsus? Radical visionary of a new age? Gender-liberating progressive? Great defender of orthodoxy? In Remembering Paul, Benjamin L. White offers a critique of early Christian claims about the "real" Paul in the second century C.E.-a period in which apostolic memory was highly contested-and sets these ancient contests alongside their modern counterpart: attempts to rescue the "historical" Paul from his "canonical" entrapments.